Generative AI and Teacher Education Programme in Nigerian Universities: Opportunities, Challenges, and Pathways to Sustainable Development - Akinwande, Eric Rotimi (Kashere Journal of Education, 2025)
The paper examines the opportunities and challenges of integrating generative AI into teacher preparation, highlighting its potential to enhance research, personalise learning, and improve pedagogical efficiency. At the same time, it underscores critical concerns such as bias in data, privacy risks, over-dependence on Technology, and the displacement of traditional cognitive skills. Drawing on global perspectives and local realities, the study situates AI within the broader context of the fourth industrial revolution and sustainable national development. It argues that, while AI offers transformative possibilities for curriculum design, instructional delivery, and academic research, its ethical use and responsible management are essential to safeguarding educational integrity. The paper recommends continuous training of faculty, the establishment of clear institutional guidelines, and the incorporation of AI literacy into curricula to ensure that Nigerian Universities harness AI as a tool for innovation rather than a threat to human agency. Ultimately, the work calls for a balanced approach that embraces AI’s benefits while mitigating its risks, positioning teacher education as a driven of sustainable development in the digital age